Removing the paint shop process: options for painting and decorating injection mouldings. (14th March 2008) - Goodship, V.; Smith, G.F.
Technological drivers exist for the complete removal of the painting process. These include satisfying changing customer requirements for multi-functional and decorative products, improved cost effectiveness and to meet stringent environmental legislation; for example in lower emissions requirements and recycling/disposal. Alternatives to the painting process are discussed. One such technology is In-Mould Decoration (IMD). This technique is attractive because a fully, or partially, decorated component is produced directly from the moulding process, with reduced emissions at lower process costs when compared to traditional techniques. A new IMD technique called IN SPIRE and its potential for energy savings compared to a paint shop is considered.